Kinetics Modeling of Glycerol Carbonate Synthesis from Glycerol and Urea over Amberlyst-15 Catalyst - Hary Sulistyo; Sabariyanto Sabariyanto; Muhammad Noor Ridho Aji; Muhammad Mufti Azis (Indonesian Journal of Chemistry, 2019)
Synthesize of glycerol carbonate from glycerol and urea is an attractive path as glycerol carbonate has a large potential as a green solvent. The aim of the present study was to develop a kinetic model of glycerol carbonate synthesis with amberlyst-15 resins as a catalyst. The investigation was carried out at various temperatures from 353 to 383 K and catalyst loading from 0.25 to 1 wt.% of glycerol. The experimental results indicated that both temperature and catalyst loading have an important effect on the glycerol conversion. According to the experimental result, the highest glycerol conversion was found 36.90% which was obtained using a molar ratio of urea to glycerol 1:3, catalyst loading of 1 wt.%, stirrer speed of 700 rpm, the temperature of 383 K and reaction time of 5 h. A kinetic model was developed based on elementary steps that take place over the catalyst. The model estimated that the pre-exponential factor was 2.89.104 mol.g–1.min–1 and the activation energy was 50.5 kJ.mol–1. By comparing the simulation and experimental data, it could be inferred that the model could predict the trend of experimental data well over the range of temperature and catalyst loading investigated in the present study.